2014
DOI: 10.1186/preaccept-2062328391321780
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutations in tumor tissue and plasma by different assays predict survival of patients with metastatic colorectal cancer

Abstract: Background: The optimal laboratory assay for detecting KRAS mutations in different biospecimens from patients with metastatic colorectal cancer (mCRC), and the clinical relevance of these gene alterations is still in question. We analyzed the prognostic-predictive relevance of KRAS status, determined in tumor and plasma DNA by two different assays, in a large mono-institutional series of mCRC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
0
12
1
Order By: Relevance
“…Even minority of healthy subjects demonstrated mutant KRAS in cfDNA [ 54 ], so the KRAS mutation used for disease diagnosis should be cautious. Generally, the prevalence of KRAS mutations in tumor tissues was high than that of cfDNA in pancreatic cancer and colorectal cancer [ 7 , 42 ]. Previous studies have suggested that the detection of tumor derived cfDNA is more trend in the setting of large tumor burden and tumor high turnover which are both independent predictors of a poor prognosis [ 38 , 48 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even minority of healthy subjects demonstrated mutant KRAS in cfDNA [ 54 ], so the KRAS mutation used for disease diagnosis should be cautious. Generally, the prevalence of KRAS mutations in tumor tissues was high than that of cfDNA in pancreatic cancer and colorectal cancer [ 7 , 42 ]. Previous studies have suggested that the detection of tumor derived cfDNA is more trend in the setting of large tumor burden and tumor high turnover which are both independent predictors of a poor prognosis [ 38 , 48 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is a leading cause of cancer mortality worldwide [ 1 ]. Many improvements have been made in screening, detection and adjuvant therapy for CRC in recent years [ 2 , 3 ]. However, the long-term survival associated with this malignant disease is not satisfactory due to tumor recurrence and metastasis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 60% of patients with mCRC carry the WT KRAS allele, and thus these patients may be appropriate candidates for therapy with EGFR inhibitors [ 4 , 8 , 9 ]. A recent study has suggested that KRAS mutation status is also predictive of long-term prognosis among patients with mCRC treated by conventional chemotherapy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%